Monoctonus leclanti sp. n. (Hymenoptera: Braconidae: Aphidiinae) from high-montane areas of southeastern Europe, and key to related species - Tomanović, Željko; Starý, Petr; Petrović, Olivera (Entomologica Fennica, 2002)
Monoctonus leclanti sp. n., a parasitoid of Delphiniobium junackianum Karsch. (Hemiptera: Aphididae) on Aconitum toxicum bosniacum and Aconitum pentheri in the high mountains of the Balkans is described. The species is an additional member of the high-montane aphid parasitoid guild determined in the area. A key to related species is included.